2015
DOI: 10.1097/lgt.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Human Papillomavirus–Based Cervical Cancer Screening

Abstract: Objective The objective of this study was to assess the conditions under which Zambia women with a history of cervical cancer screening by visual inspection with acetic acid might switch to HPV-based testing in the future. Methods We conducted a choice-based conjoint survey in a sample of women recently screened by visual inspection in Lusaka, Zambia. The screening attributes considered in hypothetical choice scenarios included: screening modality, sex and age of the examiner, whether screening results would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…DCEs typically collected preferences of a single population (42/49; 86%), most frequently the general public with mixed prior experience of screening (36/49; 73%), followed by HCPs (10/49; 20%) [41,51,52,60,61,66,67,70,74,77] with patients (9/49; 18%) [29,30,33,34,38,40,70,72,77] being considered least often. The target population of each study was reported and classified according to the authors' own definition; therefore the definition of "patients" varied and included those attending screening appointments or purchasing tests [29,30,33,34,38,40,70] and those attending appointments for other reasons [72,77].…”
Section: Quality Of Reporting Assessmentmentioning
confidence: 99%
“…DCEs typically collected preferences of a single population (42/49; 86%), most frequently the general public with mixed prior experience of screening (36/49; 73%), followed by HCPs (10/49; 20%) [41,51,52,60,61,66,67,70,74,77] with patients (9/49; 18%) [29,30,33,34,38,40,70,72,77] being considered least often. The target population of each study was reported and classified according to the authors' own definition; therefore the definition of "patients" varied and included those attending screening appointments or purchasing tests [29,30,33,34,38,40,70] and those attending appointments for other reasons [72,77].…”
Section: Quality Of Reporting Assessmentmentioning
confidence: 99%
“…Together with results from the CapU study, in which home-based urine sampling increased the participation rate by 11–16% in screening non-responders (40–65 years) after receiving two reminders [ 14 ], these data indicate that FVU sampling shows potential as liquid biopsy source to reach (non-attending) women for home-based CxCa screening. Nevertheless, it remains to be investigated how home-based FVU sampling can be ideally implemented in practice, since in contrast to the positive outcomes obtained in the studies mentioned above, a lack of privacy at home, education, place of residence (urban versus rural), and women’s concerns about collecting the self-sample properly themselves could influence the acceptability of self-sampling [ 56 ]. The use of urine sampling to monitor the impact of HPV-vaccination has also been reported, focusing on urine as a sample to assess viral endpoints [ 20 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of attributes should be explored through qualitative methods before administering the experiment. In addition, since this study began, other DCEs in African settings 44 , 45 have been published, including two conducted in Malawi. 46 , 47 They confirm the potential to apply DCEs more widely in African populations to inform policies and interventions to reduce health disparities.…”
Section: Discussionmentioning
confidence: 99%